PENGARUH TEKNIK RENDAM AIR HANGAT TERHADAP OEDEMA EKSKREMITAS BAWAH PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI - Hotmauli Hotmauli; Jihan Salsabila Anshory (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Lower extremity edema is one of the common discomforts experienced by pregnant women, particularly in the second and third trimesters. This condition is caused by an increase in body fluid volume and the pressure of the enlarging uterus, which may lead to discomfort, limit daily activities, and even trigger complications. One of the non-pharmacological management techniques that can be applied is warm water immersion therapy, which is believed to improve blood circulation and reduce fluid retention. Objective: This study aims to determine the effect of warm water immersion on lower extremity edema among pregnant women in the working area of Payung Sekaki Public Health Center. Method: The research design was pre-experimental with a one-group pretest-posttest approach. The sample consisted of 16 pregnant women in their second and third trimesters who experienced leg edema, selected using a quota sampling technique. The intervention was carried out by immersing the feet in warm water at a temperature of 37–38°C for 5–10 minutes. Results: showed that the average degree of edema before the intervention was 3.63 and decreased to 1.38 after the intervention. The Wilcoxon test obtained a p-value of 0.000 (p0.05), indicating a significant effect of warm water immersion on reducing lower extremity edema in pregnant women. Conclusion: Warm water immersion therapy is effective in reducing edema and can be considered as an alternative non-pharmacological intervention in antenatal care services.Keywords: pregnant women, edema, low extremities, warm water immersion